Disorders of the lymphatic system of the abdomen. Issue 10 (October 2016) - Patil, A.R.; Nandikoor, S.; De Marco, J.; Bhat, R.; Shivakumar, S.; Mallrajapatna, G.
Abstract : The lymphatic system of the abdomen comprises of the cisterna chyli, its major and minor lymphatic tributaries, and lymph nodes. Disorders of the lymphatic system of the abdomen are rarely encountered and consist of primary and secondary types. Abdominal lymphangiomas constitute the majority and have characteristic imaging features. Complicated lymphangiomas may pose a diagnostic dilemma. Generalised systemic lymphangiomatosis is a rare condition and affects major organs with a poor prognosis. Retroperitoneal lymphangiectasia in the appropriate setting might predict underlying infection, such as filariasis. Other acquired conditions include iatrogenic or treatment-induced chylocoele. Chylous ascites can be secondary to multiple causes and can be confirmed by biochemical testing and lymphangiogram in appropriate settings.